Cervicogenic headache: Josey's cases revisited Cefaléia cervicogênica: revisão dos casos de Josey - Maurice Vincent; Renato A. Luna (Arquivos de Neuro-Psiquiatria)
Before Sjaastad coined the term cervicogenic headache (CH) 15 years ago, neck-related headaches have been considered by different authors for many years. Even after the publication of diagnostic criteria, dispute on the clinical picture, differential diagnosis, pathophysiology and treatment of CH still persists. A paper published in 1949 by Josey reports on 6 "illustrative" cases of cervical-related headaches. Indeed, looked from a more recent perspective, those cases could eventually correspond to CH. Important topics such as the relatively high frequency, fixed unilaterality of the pain, relation to previous trauma, irradiation from the back to the forehead, normal or slightly abnormal roentgenograms, and the mechanical precipitation of attacks are some of the topics considered by Josey. The female gender was not prevalent in Josey's series. Traction and analgesics were basically the recommended treatment. CH is probably a common disorder, an idea already considered by a clinician in 1949. This syndrome was not adequately described before Sjaastad's group papers in the 80's. Muitos autores escreveram sobre cefaléias relacionadas ao pescoço antes da descrição da cefaléia cervicogênica (CH) por Sjaastad e col. Mesmo após a publicação de critérios diagnósticos, há controvérsias em relação ao quadro clínico, diagnóstico diferencial, fisiopatologia e tratamento da CH. Um artigo publicado em 1949 por Josey relata 6 casos "ilustrativos" de cefaléia relacionada ao pescoço, cujo quadro pode corresponder ao que hoje consideramos ser CH. Aspectos importantes como sua frequência relativamente elevada, unilateralidade fixa, relação a traumas prévios, irradiação póstero-anterior, normalidade de exames radiológicos e os mecanismos de precipitação foram considerados por Josey. O sexo feminino não foi predominante na sua casuística. Tração e analgésicos foram os tratamentos recomendados. CH é provavelmente uma desordem comum, o que já havia sido considerado neste estudo de 1949. A síndrome, entretanto, não foi completa e adequadamente descrita antes de Sjaastad.